2021
DOI: 10.3390/w13040411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Malachite Green on the Microbiomes of Milkfish Culture Ponds

Abstract: Intensive fish farming through aquaculture is vulnerable to infectious diseases that can increase fish mortality and damage the productivity of aquaculture farms. To prevent infectious diseases, malachite green (MG) has been applied as a veterinary drug for various microbial infections in aquaculture settings worldwide. However, little is known regarding the consequences of MG and MG-degrading bacteria (MGDB) on microbial communities in milkfish culture ponds (MCPs). In this study, small MCPs were used as a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Arias et al (2006) found that bacterial communities in a catfish aquaculture setting varied from pond to pond at a given time point. Yang et al (2021) suggested that closed pond systems usually support high fish densities and constitute a very favorable environment for the rapid spread of infectious bacteria and acute outbreaks of disease. Fern andez et al (2014) reported that the composition and diversity of the bacterial microbiota affect oysters during culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arias et al (2006) found that bacterial communities in a catfish aquaculture setting varied from pond to pond at a given time point. Yang et al (2021) suggested that closed pond systems usually support high fish densities and constitute a very favorable environment for the rapid spread of infectious bacteria and acute outbreaks of disease. Fern andez et al (2014) reported that the composition and diversity of the bacterial microbiota affect oysters during culture.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al . (2021) suggested that closed pond systems usually support high fish densities and constitute a very favorable environment for the rapid spread of infectious bacteria and acute outbreaks of disease. Fernández et al .…”
Section: Introductionmentioning
confidence: 99%